2015
DOI: 10.1177/0044118x15593668
|View full text |Cite
|
Sign up to set email alerts
|

The Role of School Culture and Basic Psychological Needs on Iranian Adolescents’ Academic Alienation: A Multi-Level Examination

Abstract: This aim of this current research was a multi-level analysis of the relationship between school culture, basic psychological needs, and adolescents' academic alienation. One thousand twenty-nine (N = 1,029) high school students from Qom City were randomly selected through a multi-phase cluster sampling method and answered questions regarding academic alienation, school culture, and basic psychological needs. Using HLM software for data analysis, the findings revealed that individual-level basic psychological n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
0
20
1
2
Order By: Relevance
“…We further hypothesized that if the need for relatedness cannot be fulfilled, students' attitudes toward learning will be affected and AL could follow. Contrary to theoretical premises and previous empirical findings indicating that students will become more involved in learning activities at school if their need for relatedness to their classmates is met (e. g., Mahmoudi et al, 2015;, we found that students' perception of peer relatedness was unrelated to AL in both primary and secondary schools. A possible explanation for this result could be that students draw on other sources to meet their need for relatedness, such as their teachers, parents, or peers outside of school (e. g., Malecki & Demaray, 2003).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We further hypothesized that if the need for relatedness cannot be fulfilled, students' attitudes toward learning will be affected and AL could follow. Contrary to theoretical premises and previous empirical findings indicating that students will become more involved in learning activities at school if their need for relatedness to their classmates is met (e. g., Mahmoudi et al, 2015;, we found that students' perception of peer relatedness was unrelated to AL in both primary and secondary schools. A possible explanation for this result could be that students draw on other sources to meet their need for relatedness, such as their teachers, parents, or peers outside of school (e. g., Malecki & Demaray, 2003).…”
Section: Discussioncontrasting
confidence: 99%
“…Secondly, we aimed at investigating the association between student needs fulfillment (as reflected by teacher competence and autonomy support, peer integration, and teacher injustice perceptions) and AL. Previous findings have shown that students' attitudes toward school and students' perceptions of needs support in the learning environments are correlated (e. g., Çağlar, 2013;Mahmoudi et al, 2015). The current study went beyond prior research by examining the quality of the associations between the aforementioned constructs and AL in two different school contexts (i. e., primary and secondary school).…”
Section: Aim Of Research and Hypothesesmentioning
confidence: 93%
See 1 more Smart Citation
“…This implies that less intrinsically motivated students tend to be more vulnerable to alienation, and it acts as external restriction that leads the individuals to the feeling of estrangement from the learning activity. Hence, Mahmoudi, Brown, Saribagloo, and Dadashzadeh (2015) concluded that the more an individual relies on external stimuli, the more likely he or she experiences academic alienation. Higgins-D' Alessandro and Sadh (1997) noted that dimensions of school culture (normative expectations, namely internalisation level and observance of school regulations by the students, student-teacher relationships, student-student relationships, and educational opportunities) were related to adolescent academic alienation.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Mahmoudi et al's (2015) study on Iranian adolescents' academic alienation found that all basic individual-level psychological needs (i.e., autonomy, competence, and relatedness) and school culture variables are significantly and negatively correlated with academic alienation. Student-student and studentteacher relationships and education service quality are negatively correlated with the levels of alienation (Mahmoudi et al, 2015;Hascher & Hagenauer, 2010). Roeser, Lord, and Eccles (1994) found that academicalienated students tended to have more negative assessments of their academic competence, negative view of the importance they attach to school, negative feelings of belonging in school and the received lower grades.…”
Section: Introductionmentioning
confidence: 99%